The Development of Neuromarketing Research on Russian Market - A. L. Beloborodova (Вестник Российского экономического университета имени Г. В. Плеханова)
Studying customer behavior has always been one of the most popular trends of marketing research. Scientists were eager to get answers to the questions: how customer makes a decision about a purchase, what drives and motivates him/her and they always wanted to learn how to influence his/her behavior and even to be able to forecast it.  The rising interest in studying customer behavior helped develop methods and methodology of marketing research. In the middle of the 20th century methods of neuroscience were already used in the field of marketing research, technologies of neuromarketing were developed and publications of research results dealing with this sphere appeared. Today’s neuromarketing research is one of fast developing trends. Debates of this topic are held in academic quarters and in business-community. Neuromarketing research abroad began its development as a separate trend in about 1924, in Russia interest in this sphere was noticed since 2009. At this time first publications on this topic turned up, but they had only a sporadic nature. Since 2015 a rise in this subject became obvious, advanced universities of the country opened 1st neurolabs and started to deal with this problem. The goal of the investigation is to study history of neuromarketing research development on Russian market and the most prominent works, authors and companies functioning in the field. The article analyzes the following issues: when and how interest in neuromarketing research appeared in Russia and what served as preconditions to their emergence and development; what technologies of neuromarketing  research are known today to science and business and which of them are the most applicable and why; who works today on Russian market of neuromarketing research; what specialization is shown by companies and what achievements they reached; what problems and restrictions are identified, which could hinder the development of neuromarketing research in the future.